Plasma Versus Whole Blood Tacrolimus Concentrations and Health-Related Quality of Life in Kidney Transplant Recipients - Svea Nolte; J. Casper Swarte; Tim J. Knobbe; Ilja M. Nolte; Tanja R. Zijp; Harmen R. Moes; Marco van Londen; Niels L. Riemersma; Johannes R. Björk; Rinse K. Weersma; Gea Drost; Stefan P. Berger; et al. (Pharmaceutics)
Background/Objectives: Tacrolimus dosing traditionally relies on therapeutic drug monitoring in whole blood, while assessment in plasma may better reflect its effect and reveal overdosing impacting health-related quality of life (HRQoL). Methods: In this cross-sectional study, 898 kidney transplant recipients (KTRs) who were at least 12 months post-transplantation were included. Plasma and whole blood tacrolimus concentrations were compared using Passing–Bablok regression analyses and Bland–Altman plots. Furthermore, the relationship with daily tacrolimus dose and with HRQoL (mental component summary (MCS), physical component summary (PCS)) was explored using linear regression by comparing standardized coefficients. Lastly, mediation analyses explored the effect of various tacrolimus-related side effects on the association between tacrolimus concentrations and HRQoL. Results: Comparison of the methods revealed a constant bias and a slight proportional bias between whole blood and plasma tacrolimus concentrations. The Bland–Altman plots indicated poor agreement with a statistically significant ratio difference (p < 0.001). Both whole blood and plasma concentrations were significantly associated with daily tacrolimus dose (both p < 0.001). Compared to whole blood tacrolimus concentrations, plasma tacrolimus concentration showed a strong negative association with worse HRQoL (PCS: st. β = −0.12, p = 0.01; MCS: st. β = −0.14, p < 0.001). The associations between plasma tacrolimus concentrations and HRQoL were mediated by fatigue severity (proportion mediated on PCS: 67.8%, MCS: 59.5%) and reduced kidney function (proportion mediated on PCS: 16.7%, MCS: 12.9%). Conclusions: In conclusion, compared with whole blood tacrolimus concentrations, plasma tacrolimus concentrations exhibited a negative association with HRQoL in KTRs. Consequently, therapeutic drug monitoring using plasma tacrolimus concentrations may reduce the occurrence of tacrolimus-related toxicity.